2019
DOI: 10.1002/mabi.201970025
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Loaded Elastin‐Like Polypeptide–Collagen Hydrogels with High Modulus for Bone Tissue Engineering

Abstract: Back Cover: Doxycycline and rhBMP‐2 loaded collagen‐elastin‐like polypeptide hydrogel is developed with high elastic modulus and anti‐microbial properties. The hydrogel has interconnected, macroporous, three‐dimensional open porous architecture. This architecture supported human adipose‐derived stem cell attachment and proliferation evidenced through rhodamine/DAPI and live/dead staining. Mineralization is observed as bright red stained particles and indicated the terminal osteogenic differentiation of cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…[ 31,32 ] It can be assumed that doxycycline and BMP‐2 would maintain a similar release profile in the current study, where the only difference in the hydrogel composition was the presence of Bioglass. This assumption is based on our observation that the SEM images in the present study (Figure 1) showed average pore diameters in both the hydrogels containing Bioglass ranged from 100 – 350 µm, which are nearly the same as shown in our previous study [ 17 ] for the ELP‐collagen hydrogels that did not contain any Bioglass. While our study was not specifically designed to determine this effect, the presence of doxycycline in our hydrogel is also beneficial in fighting post‐surgical infections and inducing bone formation.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…[ 31,32 ] It can be assumed that doxycycline and BMP‐2 would maintain a similar release profile in the current study, where the only difference in the hydrogel composition was the presence of Bioglass. This assumption is based on our observation that the SEM images in the present study (Figure 1) showed average pore diameters in both the hydrogels containing Bioglass ranged from 100 – 350 µm, which are nearly the same as shown in our previous study [ 17 ] for the ELP‐collagen hydrogels that did not contain any Bioglass. While our study was not specifically designed to determine this effect, the presence of doxycycline in our hydrogel is also beneficial in fighting post‐surgical infections and inducing bone formation.…”
Section: Discussionsupporting
confidence: 88%
“…We have previously shown that the incorporation of the high molecular weight BMP‐2 stiffened the ELP‐collagen hydrogels, likely by reinforcing intra‐ and inter‐molecular hydrogen bonding with collagen‐ELP polymeric chains. [ 17 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations